Case series: endoscopic management of benign biliary stricture - Agus Marwanto, Pigur; Noto Nugroho, Anung (International Journal of Research in Medical Sciences, 2023)
Iatrogenic bile duct injury has caused increased incidence of biliary stricture, caused by various surgeries of open, laparoscopic cholecystectomy, and transplantation procedures. Several standard procedures have been suggested to minimalize biliary tract injury and the associated morbidity from bile leakage and stricture. Endoscopic retrograde cholangiopancreatography (ERCP) has an essential role in treating biliary strictures by relieving symptoms of jaundice and cholangitis. We analyzed three cases with complaints of jaundice, itchiness, and occasional redness all over the body. The first patient had previously undergone laparoscopic cholecystectomy bile duct exploration (LCBDE) followed by stone extraction. The second patient had jaundice all over the body for two weeks before being admitted to the hospital. The patient also had a reactive hepatitis B and a history of cholecystectomy five months ago. The third patient had jaundice all over the body for the last week before being admitted to the hospital. Previously, the patient had complaints of abdominal pain and normal abdominal ultrasound. Management of benign biliary stricture (BBS) using ERCP with ballooning and plastic stent placement is effective, although repeat treatment is needed several times every 3-4 months for 1.5-2 years. Complications during follow-up were not reported, and clinical improvement was reported.